Presentation: Conflict and Peasantry in Andean Mining - Iguiñiz Echeverría, Javier (1985)
In this issue on the presence of peasants in Andean mining and on the conflicts that affect them, the articles cover a wide range of situations. In some cases, such as the one explained by R. Godoy, the peasant has a great capacity to impose his own demands and conditions in the mining activity that he himself carries out despite not being the owner of the mining resource. At the other extreme, in large mines such as those of the Southern Peru Copper Corporation, the situation of salarization is complete and subordination to the standards of mechanized and large-scale production is very great.